The Impact of an Advanced Certificate in Education (ACE) Program on the Professional Practice of Graduates - Aluko, Ruth (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2009)
This paper examines the impact of a distance education program offered by the University of Pretoria, South Africa, on the professional practice of teachers. A pilot study was conducted using a combination of surveys and focus group interviews. Findings reveal that the program was beneficial to graduates’ personal development, professional practice, schools, learners, and colleagues. Further, principals who participated in the study attested to the differences they observed between the graduates and other teachers who had not been exposed to such a program. Suggestions for improvements included the introduction of subjects taught at school as areas of specialization, involvement of school principals in the assessment of enrolled students, visits to schools by the organizers, and exposure of students to the practical opportunities offered by the program (with portfolios that could be a part of the assessment).